Reliability Estimation for Single-unit Ceramic Crown Restorations - Lekesiz, Hüseyin (Sage Publications Inc, 2014)
The objective of this study was to evaluate the potential of a survival prediction method for the assessment of ceramic dental restorations. For this purpose, fast-fracture and fatigue reliabilities for 2 bilayer (metal ceramic alloy core veneered with fluorapatite leucite glass-ceramic, d.Sign/d.Sign-67, by Ivoclar; glass-infiltrated alumina core veneered with feldspathic porcelain, VM7/In-Ceram Alumina, by Vita) and 3 monolithic (leucite-reinforced glass-ceramic, Empress, and ProCAD, by Ivoclar; lithium-disilicate glass-ceramic, Empress 2, by Ivoclar) single posterior crown restorations were predicted, and fatigue predictions were compared with the long-term clinical data presented in the literature. Both perfectly bonded and completely debonded cases were analyzed for evaluation of the influence of the adhesive/restoration bonding quality on estimations. Material constants and stress distributions required for predictions were calculated from biaxial tests and finite element analysis, respectively. Based on the predictions, In-Ceram Alumina presents the best fast-fracture resistance, and ProCAD presents a comparable resistance for perfect bonding; however, ProCAD shows a significant reduction of resistance in case of complete debonding. Nevertheless, it is still better than Empress and comparable with Empress 2. In-Ceram Alumina and d.Sign have the highest long-term reliability, with almost 100% survivability even after 10 years. When compared with clinical failure rates reported in the literature, predictions show a promising match with clinical data, and this indicates the soundness of the settings used in the proposed predictions.
Keywords: finite element analysis (FEA); restorative materials; statistics; stress analysis; CAD; biomechanics